2010
DOI: 10.1007/s10404-010-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Microfluid-induced vibration and stability of structures modeled as microscale pipes conveying fluid based on non-classical Timoshenko beam theory

Abstract: The problem of microfluid-induced vibration and instability in the walls of the micro-channels containing internal fluid is now of considerable interest for potential micro-fluidics device applications. In this article, we have studied a non-viscous and incompressible fluid through microstructures. Based on a modified couple stress theory, a non-classical Timoshenko beam model is developed for the free vibration of microstructures containing internal fluid flow, modeled as micromachined pipes conveying fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Since the classical continuum-based approach does not have a scale parameter associated with molecular interactions, it should not be utilised for structures at small-scales [6][7][8][9]. To capture the influence of molecular interactions, the classical continuum mechanics has been modified in different ways [10][11][12], leading to a number of size-dependent theories such as the pure nonlocal elasticity (PNE) [13][14][15][16][17], couple stress models [18][19][20][21][22] and nonlocal strain gradient theory (NSGT) [23][24][25][26][27]. Employing MD calculations, it has recently been shown that the NSGT is reasonable for nanostructures [28].…”
Section: Introductionmentioning
confidence: 99%
“…Since the classical continuum-based approach does not have a scale parameter associated with molecular interactions, it should not be utilised for structures at small-scales [6][7][8][9]. To capture the influence of molecular interactions, the classical continuum mechanics has been modified in different ways [10][11][12], leading to a number of size-dependent theories such as the pure nonlocal elasticity (PNE) [13][14][15][16][17], couple stress models [18][19][20][21][22] and nonlocal strain gradient theory (NSGT) [23][24][25][26][27]. Employing MD calculations, it has recently been shown that the NSGT is reasonable for nanostructures [28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in novel drug delivery fields, micro/nano-tubes could be applied for the drug transportation into the targeted organs and tumors which accelerate the curing process and can dramatically reduce the side effects of the traditional methods already being used [8]. Other applications include information technology, semiconductors, fluid storage, transport and biosensors, electromechanical devices, actuators and biology, among others [9][10][11][12][13][14][15]. Recent developments have accompanied to design and manufacture smaller micro/nano tubes which have made researchers to promote theoretical and molecular models enabling them to mathematically model such systems with satisfying precision, considering the micro/nano structure small effects which is not feasible utilizing classical continuum theories [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Kural and Özkaya [20] employed the method of multiple scales to obtain the natural frequencies in the oscillation behaviour of fluid-conveying microtubes resting on an elastic bed. Xia and Wang [21], based on the Timoshenko beam theory, analysed the motion of fluid-conveying microtubes via use of the MCS theory and the differential quadrature method to determine the critical flow velocities of the microsystem. Hosseini and Bahaadini [22] analysed the vibration behaviour of a cantilevered microtube in order to obtain the natural frequencies and mode functions for the transverse motion.…”
Section: Introductionmentioning
confidence: 99%